(3GdedGeM GdCSGSjI ddeSFhdjI GdOhdjI GdfGLeI Yf GQJcGH GdLQGFe eMd GNJUGU GdeMceI GdLfGFjI GdOhdjI ePjdG HCMOK CMcGe GdbVGA GdOhdj GdLfGFj hCMcGe GdbVGA GdOGNdj (B/s - (3Shjde, NGdO YHO GdHGSWs ((3GdbGgQI (B:s (3GdeQcR Gdbhej ddEUOGQGJ GdbGfhfjI,s, 2020)
(3GdeSFhdjI GdOhdjI GdLfGFjI Yf GQJcGH GdLQGFe eMd GNJUGU GdeMceI GdLfGFjI GdOhdjI(B-(3GdeSFhdjI GdOhdjI GdLfGFjI dQDSGA GdOhd hGdbGOI(B-(3JWHjbGJ eHOC GdeSFhdjI GdOhdjI GdLfGFjI ddbGOI(B-(3GdeSFhdjI GdLfGFjI GdLeGYjI(B-(3GdeSFhdjI GdOhdjI GdLfGFjI Yf GdeTQhY GdELQGej GdeTJQc (B[(3GdGJaGb GdLfGFj(B]-(3ehGfY GdeSFhdjI GdOhdjI GdLfGFjI(B-(3GdeSFhdjI GdOhdjI GdeOfjI Yf GQJcGH GdLQGFe eMd GNJUGU GdeMceI GdLfGFjI GdOhdjI(B-(3GdeSFhdjI GdOhdjI ddOhd hGdCaQGO Yf GQJcGH GdLQGFe eMd GNJUGU GdeMceI GdLfGFjI GdOhdjI(B-(3GdOYhi GdeOfjI VO GdCaQGO(B-(3GdOYhi GdeOfjI VO GdOhd CeGe GdeMceI GdLfGFjI GdOhdjI hGdJTQjYGJ GdOGNdjI(B-(3ETcGdjI MUGfI GdOhdI ef EbGeI GdOYGhj GdeOfjI GdNGUI HeNGdaGJ GdbhGYO GdBeQI ddbGfhf GdOhdj GdYGe(B-(3fXe MeGjI hJYhjV GdVMGjG CeGe GdeMceI GdLfGFjI GdOhdjI(B.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3GdeMceI GdLfGFjI GdOhdjIs; (3GdLQGFe GdOhdjIs; (3GdbGfhf GdOhdj GdLfGFjs